The Preliminary Survey of Avifauna in Gaya Island, Sabah, Malaysia - Jephte Sompud; Andy Immit Mojiol; Maklarin Lakim (Malaysian Nature Society, 2013)
To date, there is no updated information of the status of avifauna in Gaya Island. We have conducted a preliminary survey of birds in Gaya Island with the aim to initiate and verify the data of avifauna in Gaya Island that was published 38 years ago. A six days survey was conducted from 28 June to 3 July 2013. The main method used was mist netting. Incidental sightings of bird’s species were also recorded. Three existing trails were chosen for the survey. Four mist-nets station at 50m apart were established at each trail. The total sampling effort for mist netting for the whole survey was 45 hours. A total number of 10 species of birds from 7 families were recorded in this study. 5 families and 7 species were captured with mist-nets. The majority of the species collected are from the family of Pycnonotiidae. The result of this preliminary survey provides a general view of the communities of birds in Gaya Island.